Effectiveness of limited visual risk assessments in predicting urban tree storm failure in Wisconsin, U.S. - Larsen W. McBride; Ryan W. Klein; Andrew K. Koeser; Mysha K. Clarke; Richard J. Hauer; Thomas Ward; Timothy Bull; Chris Harchick (Urban Forestry & Urban Greening, 2026)

Attenuation of receiver ghosts in variable-depth streamer high-resolution seismic reflection data - Giuseppe Provenzano; Timothy J. Henstock; Jonathan M. Bull; Gaye Bayrakci (Marine Geophysical Research, 2020)
Receiver ghosts attenuate marine seismic reflection data at harmonic frequencies that depend on the propagation angle and the streamer depth below the sea surface. The resulting loss of bandwidth is one of the major factors hampering seismic resolution. In near-surface and legacy multi-channel data, receivers depth is often unknown and may vary significantly both along the streamer length and during the survey, making frequency–slowness deghosting techniques unsuitable. In this work, we present a method for the attenuation of receiver ghost reflections in data with an arbitrary streamer depth profile varying during the survey. For each trace, a different deghosting operator is estimated and applied at different two-way-time windows, in order to account for depth-dependent changes in reflection angles. The ghost null frequencies are picked on the time-varying power spectrum via an automatic algorithm, guided by a user-dependent a priori function, and optimised to respect the harmonics’ periodicity. The power of the inverse filter is adjusted by adaptively damping abnormal amplitudes in the deghosted spectra. The algorithm is applied to high-resolution (GI-gun, 20–400 Hz) and ultra-high-resolution (Sparker, 0.2–3.0 kHz) multi-channel datasets, yielding an excellent bandwidth recovery and gain in resolution in the final stacks. Limited computing time and straightforward application make the method widely applicable and cost-effective.

Design of a Traumatic Injury Simulator for Assessing Lower Limb Response to High Loading Rates - Spyros D. Masouros; Nicolas Newell; Arul Ramasamy; Timothy J. Bonner; Andrew T. H. West; Adam M. Hill; Jon C. Clasper; Anthony M. J. Bull (Annals of Biomedical Engineering, 2013)

Deglacial history of glacial lake windermere, UK: implications for the central British and Irish Ice Sheet - Luke J. W. Pinson; Mark E. Vardy; Justin K. Dix; Timothy J. Henstock; Jonathan M. Bull; Suzanne E. Maclachlan (Journal of Quaternary Science, 2013)
In the UK, a combination of outcrop mapping, satellite digital elevation models, high‐resolution marine geophysical data and a range of dating techniques have constrained the maximum limit and overall retreat behaviour of the British and Irish Ice Sheet (BIIS). The changing styles of deglaciation have been most extensively studied in the west and north‐western sectors of the BIIS, primarily using offshore geophysical surveys. The surviving record in the southern, terrestrial sector is fragmentary, permitting only large‐scale (tens of kilometres) and longer timescale ( c . 1 ka) reconstructions of ice‐margin movement, with limited information on deglacial processes. Here we present a high‐resolution study of the retreat behaviour for a section of the southern ice‐margin from Windermere in the Lake District, using high‐resolution two‐dimensional multi‐channel seismic data, processed using prestack depth migration. By combining the seismic stratigraphy with landform morphologies, extant cores and seismic velocity measurements, we are able to distinguish between: over‐consolidated till; recessional moraines; De Geer moraines; flowed till/ice‐front fan; supra‐/en‐glacial melt‐out till; and subsequent glaciolacustrine/lacustrine sedimentation. The results reveal a complex and active valley glacier withdrawal from Windermere that changed character between basins and produced two small, localized areas of ice‐stagnation and downwasting. This study indicates that similar active ice‐margin retreats probably took place in other valleys of the Lake District during the Late Devensian deglaciation rather than the previously held view of rapid ice‐stagnation and downwasting. When combined with the regional terrestrial record, this supports a model of early ice loss in terrestrial England compared with other parts of the UK. Copyright © 2012 John Wiley & Sons, Ltd.

Experimental Evolution of Gene Duplicates in a Bacterial Plasmid Model - Alisha K. Holloway; Timothy Palzkill; James J. Bull (Journal of Molecular Evolution, 2007)

Design of a 3D Chirp Sub-bottom Imaging System - Jonathan M. Bull; Martin Gutowski; Justin K. Dix; Timothy J. Henstock; Peter Hogarth; Timothy G. Leighton; Paul R. White (Marine Geophysical Research, 2005)

Aromatic metabolism in the fungi. Growth of Rhodotorula mucilaginosa in p-hydroxybenzoate-limited chemostats and the effect of growth rate on the synthesis of enzymes of the 3-oxoadipate pathway - Timothy J. Huber; John R. Street; Alan T. Bull; Keith A. Cook; Ronald B. Cain (Archives of Microbiology, 1975)